DISTRIBUTION OF ELAEAGNUS ANGUSTIFOLIA L. IN THE PLANT COMMUNITIES OF THE YOZYOVON NATURAL MONUMENT (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article examines the flora of the Yozyovon State Natural Monument, the structure of its plant communities, their ecological and phytocoenotic characteristics, as well as the bioecological features of Elaeagnus angustifolia occurring together with landscape-forming and rare plant species. The results of monitoring on the life forms of plant species, their habitats (biotopes), and their useful properties in the study area are presented, along with detailed information on the bioecology of Elaeagnus angustifolia. The study revealed that more than 200 plant species have been recorded within the territory of the natural monument, the majority of which are distributed in sandy and saline ecosystems.
Keywords: Elaeagnus angustifolia, Yozyovon Natural Monument, flora, desert ecosystem, plant community, monitoring, landscape, psammophyte, halophyte, phytocoenosis.